PENERAPAN STORY TELLING DAN INSTAGRAM: OPTIMALISASI LAYANAN PERPUSTAKAAN KELILING DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KEDIRI - Asri, Tri; Wulandari, Eka; Jariyah, Umi (BACA: Jurnal Dokumentasi dan Informasi, 2019)
The application of story telling in the Mobile Library of the Archives and Library Service (Disarpus) of Kediri Regency was conducted from February 2018 – March 2018 which was divided into four cycles. Each cycle consists of two meetings. At each meeting, researchers used the same story, namely stories of fables and different in each cycle with an increase of approximately two to five children per-cycle. To promote of the mobile library services, the instition used Instagram. The research results showed that the Archives and Library Service (Disarpus) of Kediri Regency has exceeded the target achievement of Instagram as a promotional media, in its application it is divided into five cycles, each cycle carried out for one week. Instagram promotions are conducted to the first cycle to the fifth cycle there is an increase from 116 to 200 followers; the achievement of likes to occur from cycle I – cycle III, from 372 to 798 likes while from cycle III until V there is not change.